How platform power undermines diversity-oriented innovation - Paula Helm (Internet Policy Review, 2024)
The paper contributes to the further development of platform studies by looking at the early stages of development. It draws on insights from an exemplary research and innovation project that aimed to develop a "diversity-aware online social platform". The article takes a co- productive stance. It is thus characterised by both critical analysis and active engagement. From this insider perspective, it discusses how emerging tensions were navigated in the attempt to develop a new diversity-oriented platform and how this affected the enactment of the idealistic motive to promote diversity that formed the initial objective for the project. The empirical observations are then engaged in conversation with insights from the fields of critical innovation and platform studies. These perspectives are mobilised to fathom how Silicon Valley agendas influence innovation imperatives that focus on rapid scalability through automation, privileging a narrow problem-solving mentality. It is argued that these imperatives limit the adoption of alternative platform models from the early stages of planning, design, and development in ways that trap innovators in the same logics that created the problems they are trying to respond to in the first place.
Keywords: 300; Innovation; Platform power; Platform design; Big data; Algorithms